Development of solid lipid nanoparticles for oral delivery of acyclovir and evaluation of its pharmacokinetics profile - Hassan, Haniza (2018)
Herpes simplex virus (HSV) type 1 and type 2 infections have become a significant global health and economic burden. These infections are life-long and symptoms of HSV infection are usually painful episodes of blisters and ulceration of skin around the infected area. Acyclovir, an antiviral drug, is prescribed to the patients in order to treat the infectious diseases. However, there are drawbacks associated with the use of acyclovir such as unwarranted high-doses-related adverse effects. Higher doses of acyclovir are given to patient in order to achieve its desired therapeutic effect, since acyclovir is known to have poor oral bioavailability. In order to improve the efficacy and oral bioavailability of acyclovir, solid lipid nanoparticles were developed as acyclovir carriers due to the advantages and its unique properties over the other colloidal drug delivery system. To date, this study is the first to design and optimize two types of solid lipid nanoparticles dispersions developed from glyceryl behanate (Compritol 888 ATO) and glyceryl palmitostearate (Biogapress Vegetal 297 ATO) using response surface methodology to encapsulate acyclovir for its oral administration. The characteristics of the solid lipid nanoparticles loaded with acyclovir and their in vivo pharmacokinetic parameters were also evaluated. Response surface methodology was used to optimize the main composition; solid lipid and surfactant, Tween 80 and their influence on three main properties of solid lipid nanoparticles, namely particle size, polydispersity index and zeta potential were investigated. The optimization process of the main compositions was carried out in order to achieve optimum solid lipid nanoparticles formulations. The data analyses showed that variation in all responses could be described as quadratic function of the composition of solid lipid nanoparticles dispersions and well fitted into a second-order polynomial model. In continuation of the optimization process, the optimized formulations, as suggested by response surface methodology were employed to fabricate acyclovirloaded solid lipid nanoparticles dispersions. The solid lipid nanoparticles from Compritol 888 ATO with particle size of 108 nm, zeta potential of -33 mV and polydispersity index of 0.22 were produced. As for Biogapress Vegetal 297 ATO, the particle size of 123 nm, zeta potential of -27 mV and polydispersity index of 0.22 were successfully fabricated. The entrapment efficiency for both formulations showed relatively good acyclovir encapsulation, between 80-90%. All formulations were stable when stored at refrigerated temperature for three months. Data from the in vitro drug release study revealed that both acyclovir-loaded solid lipid nanoparticles dispersions had prolonged acyclovir release in simulated intestinal fluid for up to 24 hours. The current study also provided in vivo oral bioavailability evidence where acyclovir-loaded solid lipid nanoparticles dispersions possessed superior oral bioavailability as compared to the commercial acyclovir suspension when given to rats. Significant increment of acyclovir concentration in rat’s plasma was seen throughout the 24-hour bioavailability study suggesting the encapsulation of acyclovir into solid lipid nanoparticles allowed a controlled release of acyclovir following its oral uptake. This study exhibited the feasibility of solid lipid nanoparticles dispersions as oral delivery vehicle for acyclovir whereby both acyclovir-loaded Compritol 888 ATO SLNs and Biogapres Vegetal 297 ATO SLNs investigated in this study have proven to enhance the absorption and oral bioavailability of acyclovir. This will therefore represent a new promising therapeutic concept of nanoparticulate delivery system for acyclovir.